2006
DOI: 10.1590/s0037-86822006000400001
|View full text |Cite
|
Sign up to set email alerts
|

An alternative antimonial schedule to be used in cutaneous leishmaniasis when high doses of antimony are undesirable

Abstract: Despite more than half a century of use in leishmaniasis, antimony therapy still presents serious problems concerning dosage and toxicity. Low and high doses have been shown to be equally effective. In this paper, the feasibility of injecting one ampoule of meglumine antimoniate intramuscularly every other day until clinical cure is demonstrated, while studying a series of 40 cutaneous leishmaniasis cases. Total dose used varied from 1,822.5 to 12,150mg of pentavalent antimony and total time of treatment varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Few studies describe the occurrence of side effects in patients receiving antimonial doses different than the conventional protocol. In a study with 40 patients receiving intramuscularly one ampoule of Glucantime ® (405 mg of antimony)/day on alternate days, up to clinical cure, only six reported side effects, mainly pain at the injection site, slight arthralgia and nausea (Oliveira‐Neto & Mattos 2006). Oliveira‐Neto et al.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies describe the occurrence of side effects in patients receiving antimonial doses different than the conventional protocol. In a study with 40 patients receiving intramuscularly one ampoule of Glucantime ® (405 mg of antimony)/day on alternate days, up to clinical cure, only six reported side effects, mainly pain at the injection site, slight arthralgia and nausea (Oliveira‐Neto & Mattos 2006). Oliveira‐Neto et al.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, there are growing reports in India, Iran, and Peru of emerging resistance to antimonials in the field [10][11][12][13][14]. Several studies have explored reducing the dose or shortening the course of antimonial treatment to improve compliance and reduce toxicities with limited success [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Latin America show significant differences in cure rates with pentavalent antimony (PA) [3, 6, 8, 2224]. It has also been reported that early treatment of ACL does not prevent the development of ulcers [25, 26] and is associated with higher treatment failure rates [26].…”
Section: Discussionmentioning
confidence: 99%